Assessing the Viability of Establishing a Dairy Milk Business in the Village Unit Cooperative of Gandusari District, Blitar Regency: A Feasibility Analysis - Novitawati, Maya; Windiana, Livia; Ariadi, Bambang Yudi (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
Milk is a vital animal-derived food product, along with meat and eggs, for human consumption. In Indonesia, the dairy industry is dominated by small and medium-sized dairies. Dairy cows are a significant source of animal protein, and their primary product is milk. In the North of Blitar Regency lies the sub-district of Gandusari, where dairy cow milk is produced in the villages under the coverage of the Village Unit Cooperative called KUD "Semen." This research was initiated to address a problem. Primary and secondary data were collected using a puIDRosive sampling technique, questionnaires, literature review, and observation. The collected data is quantitative, and investment criteria were utilized for analysis. The results of the NPV analysis showed an amount of IDR 18,672,631,280, IRR of 29%, B/C Ratio of 184.04, and PP for eight years and six days, indicating the feasibility of investing in KUD "Semen." Sensitivity analysis was performed based on three assumptions, including the increase in feed costs, operational costs, and decreased milk production of dairy cows. The analysis revealed that the dairy milk business in KUD is sensitive to increased feed prices and decreased production, among the three assumptions.